Taxation of cooperatives from the perspective of international expansion and sustainable development of social economy - Patón García, Gemma (Pontificia Universidad Católica del Perú, 2014)
The economic crisis has created a major concern in developedcountries for control of social risks with negative effects on growth and this problem can be approached from the perspective of Corporate Social Responsibility (CSR). Thus, CSR is seen as an entrepreneurial attitude aimed at promoting social, economic and environmental purposes while guarantying competitiveness in the international market. Thus, social economy can contribute to sustainable development, economic and social cohesion, to promote productive and income distribution, to ensure employment and equality of opportunities. The purpose of this study is to have an influence onthe role that taxation plays in the area of incentive policies related to social economy and very prominently manifested in the legal status of cooperatives. The approach aims to provide proposals on tax regulation of cooperatives taking the perspective of the international context and the size of the sector in countries like Spain and Peru in order to encourage cooperative social responsibility. Indeed, the importance of providing a legal and fiscal framework to promote their internationalization connects providentially with the principles that govern the cooperative action. We consider that it is essential, from the perspective of sustainable development and cooperatives’social responsibility, to take into account in the tax regime applicable criteria that can be justified on constitutional principles, the general interest of society or internationalization economic activity. Also, there could be other positive effects in the area of Latin America, such as decreasing tax evasion and the formalization of at least a portion of the informal sector of the economy, including the real impulse to CSR.